Unraveling a rare medical anomaly: a case report on the incidental discovery of a mixed fungal ball with parasitic elements - Ahmed, Saud; Kunnumal, Ayisha; Koratagere, Prathima; Rane, Vishakha Vijay (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Fungal ball is a type of fungal rhinosinusitis (FRS) that is chronic, non-invasive, and extramucosal. A fungal ball is a non-invasive accumulation of dense conglomeration of fungal hyphae in one sinus cavity Sinonasal fungal ball is known to be the most common form of fungal sinusiti. It typically affects immunocompetent individuals and appears as a unilateral lesion between the fourth and sixth decades of life. The most commonly involved sinus is the maxillary sinus. Patients are often asymptomatic, but some patients develop chronic mucopurulent rhinorrhea. Treatment is surgical, with removal of the fungal contents of the involved sinus, and no subsequent treatment is indicated, given the process is noninvasive. Here in we report the case of a 64-year-old gentleman diagnosed with fungal ball of maxillary sinus. Patient was asymptomatic and the fungal ball was identified as an incidental finding on imaging for stroke. The histopathological examination necrotizing lesion showing entangled septate, aseptate and pigmented fungal structures and non-viable parasitic structures noted. No viable tissue was seen.